El Niño Driven Changes in Global Fire 2015/16 - Burton, Chantelle; Betts, Richard A.; Jones, Chris D.; Feldpausch, Ted R.; Cardoso, Manoel; Anderson, Liana O. (Frontiers in Earth Science, 2020)
El Niño years are characterised by a high sea surface temperature anomaly in the Equatorial Pacific Ocean, which leads to unusually warm and dry conditions over many fire-prone regions globally. This can lead to an increase in burned area and emissions from fire activity, and socio-economic and environmental losses. Previous studies using satellite observations to assess the impacts of the recent 2015/16 El Niño found an increase in burned area in some regions compared to La Niña years. Here, we use the dynamic land surface model JULES to assess how conditions differed as a result of the El Niño by comparing simulations driven by observations from the year 2015/16 with mean climatological drivers of temperature, precipitation, humidity, wind, air pressure and short and long-wave radiation. We use JULES with the interactive fire module INFERNO to assess the effects on precipitation, temperature, burned area, and the associated impacts on the carbon sink globally and for three regions: South America, Africa and Asia. We find that the model projects a variable response in precipitation, with some areas including northern South America, southern Africa and East Asia getting drier, and most areas globally seeing an increase in temperature. As a result, higher burned area is simulated with El Niño conditions in most regions, although there are areas of both increased and decreased burned area over Africa. South America shows the largest fire response with El Niño, with a 13% increase in burned area and emitted carbon, corresponding with the largest decrease in carbon uptake. Within South America, peak fire occurs from August to October across central-southern Brazil, and temperature is shown to be the main driver of the El Niño-induced increase in burned area during this period. Combined, our results indicate that although 2015/16 was not a peak year for global total burned area or fire emissions, the El Niño led to an overall increase of 4% in burned area and 5% in emissions compared to a ‘No El Niño’ scenario for 2015/16, and contributed to a 4% reduction in the terrestrial carbon sink.